Efficient and multiplexable genome editing using Platinum TALENs in oleaginous microalga, Nannochloropsis oceanica NIES‐2145. (30th September 2020) - Kurita, Tomokazu; Moroi, Keishi; Iwai, Masako; Okazaki, Kumiko; Shimizu, Shinsuke; Nomura, Seiji; Saito, Fumihiko; Maeda, Shinichiro; Takami, Akihide; Sakamoto, Atsushi; Ohta, Hiroyuki; Sakuma, Tetsushi; et al.
Abstract: Algae accumulate large amounts of lipids produced by photosynthesis, and these lipids are expected to be utilized as feedstocks for sustainable new energies, known as biodiesels. Nannochloropsis species are eukaryotic microalgae that produce high levels of lipids. However, since the production costs of algal biodiesels are higher than those of fossil fuels, the improved productivity of algal lipids by molecular breeding of algae is required for practical use. In the present study, we developed a highly efficient genome‐editing system involving Platinum transcription activator‐like effector nucleases (TALENs) in Nannochloropsis oceanica . Platinum TALENs codon‐optimized for N. oceanica were synthesized, and their DNA‐binding activity was confirmed by single‐strand annealing assays in human HEK293T cells. All‐in‐one expression vectors for Platinum TALEN targeting the nitrate reductase gene, NoNR, and acyltransferase gene, LPAT1, were transfected into Nannochloropsis species. The introduction of each Platinum TALEN revealed high genome‐editing efficiency with no detectable off‐target mutations at the candidate sites in N. oceanica . By simultaneously introducing TALENs targeting two genes, we obtained double mutant strains. The loss‐of‐function phenotype of NoNR was also confirmed. These findings will provide an essential technology for molecular breeding in Nannochloropsis species. Abstract : Transfection of all‐in‐one expression vectors for Platinum TALEN targeting the nitrate reductase gene, NoNR, and acyltransferase gene, LPAT1, into Nannochloropsis species revealed high genome editing efficiency with no detectable off‐target mutations. By simultaneously introducing TALENs targeting two genes, we obtained double mutant strains. These findings will provide an essential technology for molecular breeding in Nannochloropsis species.